Rights for house buyers - Md Dahlan, Nuarrual Hilal (New Straits Times, 2008)
A ROOF over the head, a shirt on the back, food on the table and access to healthcare and education are among the basic needs of a citizen that a government is responsible for, and these needs have generally been taken care of all these years.In the case of the roof over your head, the government has since the 1970s been actively working together with the private sector to promote home ownership. Since that time, government efforts have been sullied by some housing developers and it is not just the occasional lapses.The national House Buyers Association has a list of complaints made to it, ranging from non-issuance of strata titles, poor management and maintenance, shoddy workmanship and, perhaps worst of all, abandonment of housing projects. In 2006, of the 245 projects involving 38,744 house buyers, 30 per cent of the complaints involved non-issuance of strata titles, 24 per cent were on management and maintenance, and 14 per cent on abandoned projects.